Manusia yang Beradab Menurut Tri Kaya Parisudha - Felix Mahendra (Journal Social and Humaniora, 2023)
The focus of this study aims to explore the deepest meaning of civilized humanity in the second principle of Pancasila, namely "Just and civilized humanity" in the teachings of Tri Kaya Parisudha. This is one of the efforts to explore the values ??of Pancasila contained in Indonesian local wisdom, as Soekarno emphasized that he was not the creator of Pancasila, but the digger of Pancasila. The researcher responded to this by exploring the teachings of Tri Kaya Parisudha as the cultural-religious wisdom of the Balinese people which is always used both in character education in schools and everyday life. This research is descriptive-qualitative research with a literature review method. The data used in this study were collected from books, journals, and scientific articles. This study found that the concept of Tri Kaya Parisudha has a positive-correlative relationship with Pancasila, especially in the second principle which reads: "Just and civilized humanity". In addition, Tri Kaya Parisudha is one of the paradigms that can be used in building national character for all Indonesian people.